Developing e-learning based on animation content to improve students’ mathematical connection abilities - Rusdyi Habsyi; Rusmin R.M Saleh (SAINTIS Publishing, 2022)
Mathematical connection capabilities are part of an interconnected network of interconnected knowledge packages of interconnected knowledge packages of knowledge packages consisting of key concepts for understanding and developing relationships between mathematical ideas, concepts, and procedures. The purpose of this paper is to develop e-learning based on animation content to improve mathematical connection abilities in senior high school students. The e-learning was developed using framework proposed by Moodle, while the animation content was developed using macromedia flash. To get the student mathematical connection abilities, pretest and posttest were administered before and after teaching and learning process. The data were analyzed using t-test and found that e- learning which was based on animation content not only had significant effect on mathematical connection abilities but also been able to improve students’ mathematical connection abilities far better than that of conventional approach. From the posttest results show that the total score of mathematical connection abilities presented shows that the average posttest of mathematical connection abilities is 72.9 e-learning based on animation content, this shows that e-learning based on animation content can improve mathematical connection skills students with e-learning.